FROST INVESTIGATION 1945-1946. COMPREHENSIVE REPORT. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1947)
The frost investigation program for the fiscal year 1945-1946 was conducted by the Frost Effects Laboratory in the New England Division with the cooperation of the Great Lakes Division and the Missouri River Division. Field investigations were made at nine airfields, with varying subsurface conditions, located in the northern part of the United States and laboratory studies at the Frost Effects Laboratory. This report contains a method of predicting the depth of frost penetration, based upon the properties of the soils encountered. A study of the pavement failures which were caused by frost action or to which frost action was a contributing cause is presented. (Author) See also Appendix 1, AD-712 356.